A Study on Dental Caries and Dental Plaques Caused by Streptococcus Mutans, of Patients at Border Guard Hospital Dhaka, Peelkhana - Jasmine, Rezina; Mridha, Khairul Islam; Akhter, Mohammad Kamal; Sharmin, Dilruba (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: Dental caries is one of the most common chronic infectious diseases in the world. The acids generated through the fermentation of sugar by the microorganisms in dental plaque can decalcify the superficial layers of tooth enamel and can initiate dental caries. Streptococcus mutans have been proposed as the main etiological agents of dental caries .The aim of this study is to identify the main etiological agents of dental caries and plaque which are supposed to be Streptococcus mutans as correlating microorganism. Materials and Methods: This cross sectional study was carried out in the Pathology department of Border Guard Hospital, Peelkhana, Dhaka during the period of 1st October, 2018 to 3IST December,2018. Study population was newly enrolled soldiers and their families as male ,female and children in BGB. A total of 50 clinical samples were included in this study. The samples were collected from the Dental outdoor patient department and all laboratory tests were performed at Pathology department of aforementioned hospital. After performing all possible microbiological tests for bacterial isolation, results were recorded. Results: Among 50 samples, 46(92%) samples are considered to be positive for Streptococcus viridans and 27(54%) isolates are identified as Streptococci mutans according to ability of producing special kind of exopolysaccharide, lactic acid formation and high salt tolerance tests. Associated organisms (32%) like candida were present in 15(30%) samples and other bacterial colonies were present in 31(62%) samples, along with Streptococcus viridans. Conclusion: The finding of this study will help the dentists to treat the patients with chronic caries, dental plaques as they pose the gravest threat when they settle down on damaged heart valves, cause subacute bacterial endocarditis and other infections in various sites including mouth, joints, skin, muscle, and central nervous system after tooth extraction or any other invasive procedure J Bangladesh Coll Phys Surg 2020; 38(3): 121-125